Kreativitas Guru melalui Pelatihan Pembuatan Media Pembelajaran Tematik Sederhana - Nurita Apridiana Lestari; Utama Alan Deta (Jurnal Pemberdayaan Masyarakat, 2022)
The training activities aim to develop teachers' creativity in making simple media for thematic learning. 21 teachers participated in training activities for making simple media for good thematic learning. The training method begins with studying learning tools, especially the lesson plans applied and studying thematic materials at all grade levels. The action is continued by determining the appropriate learning media and preparing tools and materials for making simple thematic learning media. Teachers are trained to make learning media, and an assessment of the performance of teacher creativity is carried out during the process of making the media. Based on the results of the creativity performance assessment, it was found that the teacher was able to design learning media designs very well and in accordance with the specified theme. Teacher trainees can determine tools and materials very precisely to create simple thematic learning media. In the process of making media, the teacher carries out the stages of making media well. The training activities were very high with the enthusiasm of the teachers in the training activities. In addition, teachers can communicate well the results of making simple thematic media in training.